Gambaran kepuasan pernikahan pada wanita keturunan Arab yang melakukan pernikahan dengan etnis lain - Ragoan, Syarifah; Untoro, Vinaya; Ari, Diana Rita (Konsorsium Psikologi Ilmiah Nusantara, 2017)
The present study intends to describe the dynamics of marital satisfaction of women of Arabian descent who married a spouse of another ethnicity. The marriage of women of Arabian descent with someone from a different ethnicity is considered as breaking the cultural norms. In the present study, marital satisfaction consists of many aspects, namely communication, the personality of the spouse, the ability to solve conflicts, sexual relationship, leisure activity, the presence of children and parenting, financial management, role suitability, religious orientation, as well as family and friends. The present study employed qualitative methods with 2 participants. Participants were women of Arabian descent who married someone from another ethnicity for two to five years and at least graduated from high school. Data were gathered through interview and observation. The results showed that participants feel uncomfortable due to their marriage being disapproved by their extended family, however it does not seem to influence their marital satisfaction significantly. The most significant factor influencing marital satisfaction of both participants was financial or economic factor.